The birds of Salayar and the Flores Sea Islands - Guy Dutson (Indonesian Ornithologists’ Union, 1995)
The islands of Salayar, Bonerate and Kalaotoa were visited for a few hours and the island of Tanahjampea for two days between 23 and 26 September 1993. Although only limited time was available for bird observations, a number of species new for each island were observed and the conservation status of the forest birds was assessed. These islands, according to current taxonomic opinion, host one endemic species, White-tipped Monarch Monarcha everetti, in addition to many endemic subspecies and populations of some widespread but threatened species.